Study of fetal and maternal outcome and associated risk factors in elderly primigravida pregnant women at tertiary care center in Western Rajasthan - Shweta Sharma; Shishram Saini; Rizwana Shaheen; Asmita Arun; Neetu Gehlot; Kirti Gupta (Asian Journal of Medical Sciences, 2025)
Background: Elderly primigravida is one aged 35 or more at first delivery. Elderly primigravida combines the concerns of advanced maternal age with those of obstetrically untested primigravida. While the risks related to multiple pregnancy and previous pregnancy are not applicable, there is an added dimension of precious pregnancy reflecting concern this pregnancy maybe the one and only opportunity to have a child. Aims and Objectives: The aims and objectives of the study are to determine antenatal complications among elderly primigravida woman and maternal and fetal outcome associated with pregnancy in elderly primigravida women. Materials and Methods: A prospective observational study was conducted in the Department of Obstetrics and Gynaecology at Umaid Hospital, Jodhpur, on 90 patients during the period of February 2024–July 2024 at Umaid Hospital, Jodhpur, in primigravida females of age 35 or more having their first delivery at Umaid hospital. Patients who gave consent and satisfied inclusion criteria were included in study. Results: Mean age of patient was 36.7 years and mean gestational age of delivery was 37.1 weeks. Major cause of delayed conception was infertility (58.9%) followed by late marriage (40%) and career preference (1.1%). Common antenatal obstetric complications in elderly primigravida were HDOP (28.8%), oligohydramnios (17%), gestational diabetes mellitus (14.4%), and preterm labor (11%). Twin pregnancies were significantly higher in patients aged 40 and above (58.3%) compared to younger patients. Conclusion: The study shown that advanced maternal age pregnancy is a high risk pregnancy which needs special care and more careful antenatal monitoring. Significantly higher incidence of hypertensive diseases in pregnancy and twin gestation was seen with increasing maternal age.